The Role of Vector Trait Variation in Vector-Borne Disease Dynamics - Cator, Lauren J.; Johnson, Leah R.; Mordecai, Erin A.; El Moustaid, Fadoua; Smallwood, Thomas R. C.; LaDeau, Shannon L.; Johansson, Michael A.; Hudson, Peter J.; Boots, Michael; Thomas, Matthew B.; Power, Alison G.; Pawar, Samraat (Frontiers in Ecology and Evolution, 2020)
Many important endemic and emerging diseases are transmitted by vectors that are biting arthropods. The functional traits of vectors can affect pathogen transmission rates directly and also through their effect on vector population dynamics. Increasing empirical evidence shows that vector traits vary significantly across individuals, populations, and environmental conditions, and at time scales relevant to disease transmission dynamics. Here, we review empirical evidence for variation in vector traits and how this trait variation is currently incorporated into mathematical models of vector-borne disease transmission. We argue that mechanistically incorporating trait variation into these models, by explicitly capturing its effects on vector fitness and abundance, can improve the reliability of their predictions in a changing world. We provide a conceptual framework for incorporating trait variation into vector-borne disease transmission models, and highlight key empirical and theoretical challenges. This framework provides a means to conceptualize how traits can be incorporated in Vector Borne Disease systems, and identifies key areas in which trait variation can be explored. Determining when and to what extent it is important to incorporate trait variation into vector borne disease models remains an important, outstanding question.